Light fuels while nitrogen suppresses symbiotic nitrogen fixation hotspots in neotropical canopy gap seedlings. Issue 5 (7th July 2021) - McCulloch, Lindsay A.; Porder, Stephen
Summary: Mature neotropical lowland forests have relatively lower symbiotic nitrogen fixation (SNF) rates compared with secondary forests. Canopy gap formation may create transient SNF hotspots in mature forests that increase overall SNF rates in these ecosystems, as canopy gaps are pervasive across the landscape and increasing in frequency. However, what environmental conditions are driving SNF upregulation in canopy gaps is unknown. In a field experiment to test these potential environmental controls on SNF, we grew 540 neotropical nitrogen‐fixing legume seedlings ( Pentaclethra macroloba, Zygia longifolia, and Stryphnodendron microstachyum ) under manipulated light and soil nitrogen availability in canopy gaps and intact forests at La Selva Biological Station, Costa Rica. Seedling biomass, nodule biomass, and SNF (g N seedling −1  h −1 ) were 4‐, 17‐ and 42‐fold higher, respectively, in canopy gaps than in the intact forest. Nitrogen additions decreased SNF, but light had a stronger positive effect. Upregulation of SNF in canopy gaps was driven by increased plant growth and not a disproportionate increased SNF allocation. These data provide evidence that canopy gap SNF hotspots are driven, in part, by light availability, demonstrating a potential driver of SNF spatial heterogeneity. This further suggests that canopy gap dynamics are important for understanding the biogeochemistry of neotropical forests.